Peran dan Fungsi Jaksa dalam Penegakan Etika dan Perilaku: (Studi Kasus Kejaksaan Tinggi Kalimantan Tengah) - Andini Putri Lestari; Maulida Khairunisa; Muhammad Fauzan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article discusses the role and function of prosecutors in enforcing ethics and behavior, with a case study at the Central Kalimantan High Prosecutor's Office. This research analyzes how the Central Kalimantan High Prosecutor's Office carries out internal and external oversight functions to ensure the ethical and professional behavior of prosecutors. The research results show [mention the main findings briefly, for example: the effectiveness of existing monitoring mechanisms, obstacles faced, and recommendations for improvement]. This study contributes to a better understanding of the importance of integrity and accountability in the justice system, especially in the context of law enforcement in Indonesia.